Analisis Persepsi Konsumen - Subakti, Agung Gita; Tenironama, Darwin; Yuniarso, Ari (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
Loewy is one of the restaurants and bars in Jakarta who serves drinks to the concept of molecular mixology. Molecular mixology itself developed in conjunction with the method of Molecular gastronomy which is a scientific study about gastronomy or the branch of science that studies the transformation of physiochemical on food during the cooking process and the phenomenon of knowledge as they consumed. However, molecular mixology is not as popular as molecular gastronomy where the general public still have yet to understand or even be aware of drinks made with this method. Therefore, the researchers want to do an analysis on consumer perceptions of product of molecular mixology in Loewy Jakarta. The research method used is descriptive methods. This is done to obtain a systematically and factual. By this study, it is expected to know the consumers’ perception in Loewy Jakarta on beverage products made with the molecular mixology method.